A Simple and Effective Method for Flow Cytometric Study of Lymphoid Malignancies Using Needle Core Biopsy Specimens. Issue 5 (1st April 2018) - Chi, Pei‐Dong; Freed, Natalie S.; Wake, Laura; Page, Cynthia; Smith, Lynette M.; Amador, Catalina; Qureishi, Hina Naushad; Greiner, Timothy C.; Rodig, Scott J.; Pirruccello, Samuel J.; Yuan, Ji; Fu, Kai
Abstract : Objectives: We developed a simple and effective rinsing technique (RT) of needle biopsies to produce cell suspensions for flow cytometry (FCM) and evaluated whether the RT is comparable to the conventional tissue cell suspension (TCS) technique. Methods: We retrieved 93 needle core biopsy cases employing the RT for FCM and 25 needle biopsy cases using TCS for FCM. Results: The diagnostic concordance between the FCM results and the morphologic diagnoses of both groups was compared. The diagnostic concordance was comparable in the RT group (92.6%) to the TCS group (71.4%). Furthermore, the diagnostic concordance in the RT group was associated with number of isolated cells. The diagnostic accuracy increased significantly when the cell number was above 30, 000 in the RT group. Conclusions: The RT for FCM not only maximizes the tissue utilization, but also is a simple and effective method to obtain cell suspension as compared to traditional cell suspension technique. © 2018 International Clinical Cytometry Society